2009
DOI: 10.1093/ndt/gfp623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renal volume and single-kidney glomerular filtration rate on renal functional outcome in atherosclerotic renal artery stenosis

Abstract: Our data suggest that, after revascularization, GFR improvement is likely if there is a disproportionately higher baseline PV:SK-GFR in the RAS kidney. Analysing these parameters can potentially identify these 'hibernating' kidneys and aid determination of renal functional outcome in RAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Kidney morphology is related to estimated glomerular filtration rate (eGFR) in patients with chronic kidney disease (CKD) (2)(3)(4), in obesity subjects (5), and in patients with nephrectomy due to renal tumor (6,7). Kidney morphology is also related to albuminuria (4) in CKD patients and related to the improvement of renal function after angioplasty in patients with renovascular hypertension (8). These studies suggested that kidney morphology could be closely related to eGFR or proteinuria when the kidney is in a pathological state, In addition, they suggested that the relationship between pathological findings derived from fresh tissues of living patients and kidney morphology could possibly contribute to the explanation of the relationship between kidney morphology and eGFR or between kidney morphology and proteinuria in patients with nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney morphology is related to estimated glomerular filtration rate (eGFR) in patients with chronic kidney disease (CKD) (2)(3)(4), in obesity subjects (5), and in patients with nephrectomy due to renal tumor (6,7). Kidney morphology is also related to albuminuria (4) in CKD patients and related to the improvement of renal function after angioplasty in patients with renovascular hypertension (8). These studies suggested that kidney morphology could be closely related to eGFR or proteinuria when the kidney is in a pathological state, In addition, they suggested that the relationship between pathological findings derived from fresh tissues of living patients and kidney morphology could possibly contribute to the explanation of the relationship between kidney morphology and eGFR or between kidney morphology and proteinuria in patients with nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…These measurements have been difficult to confirm in any absolute way. Some have suggested that an index of kidney volume as determined by magnetic resonance with relatively reduced function by radionuclide scan may identify hibernating renal tissue (17). We have been impressed that advancing vascular occlusion does, indeed, produce cortical hypoxia at some point, which was illustrated using BOLD magnetic resonance in the right kidney ( Figure 4); it activated inflammatory injury pathways with accumulation of macrophages, which is known to attract T lymphocytes within the renal parenchyma (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies suggest that it may be possible to identify kidneys with hibernating parenchyma before tissue is irretrievably damaged; one technique involves examining the ratio of parenchymal volume (measured by MRI) with isotope single kidney GFR values [ 71 ] (a highvolume:GFR signifying a kidney capable of improving its function with renal revascularization). In the future such techniques may help identify patients in the early and potentially modifi able stages of the natural history of their disease.…”
Section: Identifi Cation Of At-risk Organs Earlier In the Natural Hismentioning
confidence: 99%